2020
DOI: 10.1159/000509133
|View full text |Cite
|
Sign up to set email alerts
|

Application of “Tissueoid Cell Culture System” Using a Silicate Fiber Scaffold for Cancer Research

Abstract: Background: We developed a 3-dimensional (3D) culture system using a high-purity silica fiber scaffold of unwoven sheets called Cellbed TM. Methods: We used adherent colon and esophagogastric junction adenocarcinoma cells, tongue squamous cell carcinoma (SqCC) cells, and nonadherent gastric cancer cells. These cells were subjected to staining with various substances and observed by electron microscopy. To evaluate the effects of extracellular matrix in carcinoma tissues, SqCC cells were cultured in Cellbed coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Therefore, it remains challenging to perform the 3D culture of fibroblasts and vascular endothelial cells in Cellbed. Nonetheless, it is to some extent possible to simulate the interstitium by coating Cellbed with collagen, laminin and fibronectin [ 10 ]. The function of 3D-cultured rat hepatocytes grown in Cellbed and coated with these lasts longer in 3D than in 2D [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it remains challenging to perform the 3D culture of fibroblasts and vascular endothelial cells in Cellbed. Nonetheless, it is to some extent possible to simulate the interstitium by coating Cellbed with collagen, laminin and fibronectin [ 10 ]. The function of 3D-cultured rat hepatocytes grown in Cellbed and coated with these lasts longer in 3D than in 2D [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are various types of scaffold materials available, we recently developed a tissueoid cell culture system [ 10 ] using a 3D culture scaffold Cellbed TM (Japan Vilene, Tokyo, Japan) that consists of highly pure silicate fiber. Previous 3D culture studies of various cancer cell lines, such as colorectal cancer, Barrett′s adenocarcinoma, gastroesophageal junction cancer, gastric cancer and tongue cancer, have shown that 3D culture systems allow good morphological observations resembling in vivo conditions [ 10 ]. Cellbed is an approximately 200-µm-thick ultrafine nonwoven fiber scaffold [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there have been reports on 3D cancer organoids and cancer tissue‐originated spheroids using ECM matter such as spheroids and collagen 6 . We also have recently proposed a novel 3D “tissueoid cell culture system” using Cellbed (Japan Vilene Co.) as a 3D culture carrier 7,8 . Cellbed is a fiber aggregate made of ultrafine silica fiber, and its structure is similar to that of the tissue skeleton of loose connective tissue in a living body 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Silica fibers coated with different types of collagen were used to culture different types of cancer cells in the 3D environment where cells showed enhancement of invasiveness and proliferation when the fibers were coated with collagen IV. This method was called "tissueoid cell culture system" and suggested for its advantages of combability with different cell staining methods [98]. Cell culture vessels were also modified into hydrophobic fluoro-silica (FS) surface resulting in low adherence and transient aggregation of breast cancer cells followed by disaggregation.…”
Section: Gelatin Fibrin Alginate and Agarosementioning
confidence: 99%